2020
DOI: 10.4314/jae.v24i4.12
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing adoption of sustainable soil and water conservation practices among smallholder farmers in Kwara State, Nigeria

Abstract: The study examined the adoption of water conservation practices and challenges encountered by smallholder farmers in water resource conservation in Enyibe, Ermelo South Africa. The data were collected using structured questionnaires, observation and focus group discussion. Frequency, mean and logistics regression were used for data analysis. Age (β=1.238), sex (β=-1.497), level of education (β=-1.062), access to irrigation facilities (β=1.690), payment of water tariff (β=1.369) and agricultural extension advic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Preferred tree species for agroforestry were Cedrus deodara and Grevillea robusta. Iyilade et al [45] found that gender was also associated with adoption of conservation practices in Nigeria. Belachew et al [30] found that female household heads were more likely to adopt strip cropping and older household heads were less likely to adopt soil bunds in Ethiopia.…”
Section: Associations Among Farmer Characteristicsmentioning
confidence: 99%
“…Preferred tree species for agroforestry were Cedrus deodara and Grevillea robusta. Iyilade et al [45] found that gender was also associated with adoption of conservation practices in Nigeria. Belachew et al [30] found that female household heads were more likely to adopt strip cropping and older household heads were less likely to adopt soil bunds in Ethiopia.…”
Section: Associations Among Farmer Characteristicsmentioning
confidence: 99%
“…01, January and 2024: pp. 208-215 209 [13], [14]. By critically evaluating the existing body of research, this analysis aims to elucidate the nuances of how sustainable agricultural practices contribute to or hinder the economic sustainability of farmers across diverse geographical and socio-economic contexts [15], [16].…”
Section: Introductionmentioning
confidence: 99%